The Psychological Pressures of Breast Cancer Patients During the COVID-19 Outbreak in China—A Comparison With Frontline Female Nurses - Cui, Qin; Cai, Zhongxiang; Li, Juanjuan; Liu, Zhongchun; Sun, Shengrong; Chen, Chuang; Wang, Gaohua (Frontiers in Psychiatry, 2020)
Objective: During the outbreak of the COVID-19 epidemic in China, breast cancer (BC) patients and healthcare workers faced several challenges, resulting in great psychological stress. We measured the psychological status of BC patients and female nurses and compared the severity within the two groups at the peak time-point of the COVID-19 outbreak. Methods: A total of 207 BC patients and 684 female nurses were recruited from Wuhan. They completed an anonymous questionnaire online using the most popular social media software in China, WeChat. The psychological status of BC patients and of female nurses was measured using the Chinese versions of the 9-item Patient Health Questionnaire (PHQ-9), the 7-item Generalized Anxiety Disorder scale (GAD-7), the 7-item Insomnia Severity Index (ISI), and the 22-item Impact of Event Scale-Revised (IES-R) for evaluation of post-traumatic stress disorder (PTSD). The differences between the two groups were analyzed. Results: The scores of BC patients and frontline female nurses for the four scales were significantly higher than those of non-frontline female nurses (P < 0.001). There were similar scores between BC patients and frontline female nurses for PHQ-9, GAD-7, and IES-R (P = 0.789, P = 0.101, P = 0.158, respectively). Notably, the scores of BC patients for ISI were significantly higher than those of the frontline female nurses (P = 0.016). A considerable proportion of BC patients reported symptoms of depression (106/207, 51.2%), anxiety (130/207, 62.8%), insomnia (106/207, 51.2%), and PTSD (73/207, 35.5%), which was more severe than that of female nurses. Conclusions: BC patients experienced great psychological pressure during the COVID-19 outbreak. The incidents of symptomatic anxiety, depression, sleep disorders, and PTSD were significantly comparable to that of frontline female nurses, and episodes of insomnia among BC participants were more serious than for frontline female nurses.